Password Code and Fingerprint Based Security Using Relay - Abdul Rahim, Muhammad Nazmi; Bohari, Dr. Azuwien Aida (Progress in Engineering Application and Technology, 2022)
This project focusing on security system and the implementation is more to industrial site such as manufacturing plant or site that have a mega machine that must turn on and shut down carefully. By using a password and fingerprint scanner can reduce the chance to fatal injury because of only the person in charge that can turn on or off the system. Electrical engineer protection using user changeable password based and fingerprint scanner to trigger the circuit breaker. A circuit breaker is an automatically operated electrical switch designed to protect an electrical circuit from damage caused by overload or short circuit. Its basic function is to detect a fault condition or interrupt current flow. A keypad and fingerprint scanner are used to authorize the input and a relay to open or close circuit breaker, which is indicated by a lamp.